Gestión de la seguridad hospitalaria en unidades de atención pediátrica (2016)
Introduction: security risks are a major source of injuries and deaths among workers and the general public worldwide; health facilities are not immune to this problem, so implementation and assessment of hospital safety management is required. Objective: to determine the hospital safety conditions resulting from the safety management processes. Methods: multicenter evaluation study with a quantitative approach carried out at two pediatric care units of Santa Marta City (Colombia); data was collected by applying a verification tool, built and based on the safety standards defined in the Colombian legislation (Guía Técnica Colombiana 045, a technical annex for verification of quality conditions resulting from the resolution 1043 of 2006, and Technical Regulations for Electrical Installations). Analysis of the information obtained was performed using SPSS 20.0, with output to charts and graphs through descriptive statistics. Results: in both facilities, we found high risk for floods, armed assaults and fire; medium risk for avalanche, landslides and earthquakes; low risk for volcanic eruptions; average risk of falls on floors and aisles, low risk in electrical safety; also low responsiveness to emerging events response. However, we observed appropriate room-enabling standards. Conclusions: of patient safety management is a process that is deficient by actors in the facilities, proving hospital safety risk in pediatric care units. © 2016, Editorial Ciencias Medicas. All rights reserved.